Simulation-based education model for under-resourced nursing education institutions in Lesotho - Pule S. Moabi; Ntombifikile G. Mtshali (AOSIS, 2022)
Background: The changing landscape of nursing education to competency-based education has strengthened the importance of simulation learning in the process of developing the required graduate competencies. Aim: This study aimed to develop a model that guides the implementation of simulation-based education (SBE) in under-resourced nursing education institutions in Lesotho. Setting: Four Nursing Education Institutions in Lesotho. Methods: An explanatory sequential mixed methods design was adopted. Sampling methods included stratified systematic random, purposive and systematic sampling. The total sample was 390 comprising students, nurse educators and principals. Data were collected through questionnaires, focus group discussions and in-depth unstructured individual interviews. Statistical analysis was employed for quantitative data while a grounded theory approach guided the qualitative data analysis and model development. Results: Implementation of simulation emerged as a multilevel, multi-actor and multistage process of adopting, introducing and implementing SBE. This education takes place in a simulated environment that serves as a connecting bridge between the learning of theory in the classroom and clinical learning in real-life settings. The model generated from this study has simulation implementation as the main concept that is supported by four major concepts: (1) simulation initiation at the strategic level, (2) simulation implementation at the tactical level, (3) simulation implementation at the operational level and (4) simulation outcomes. Conclusion: Successful implementation of simulation requires buy-in from key stakeholders. Simulation-based education policy, competent facilitators and a well-resourced clinical skills laboratory may facilitate the development of the required competencies. Contribution: The study provides guidance on how SBE can be implemented in resource-limited settings.